Anti-Müllerian hormone concentrations and antral follicle counts for the prediction of pregnancy outcomes after intrauterine insemination. Issue 1 (April 2016) - Moro, Francesca; Tropea, Anna; Scarinci, Elisa; Leoncini, Emanuele; Boccia, Stefania; Federico, Alex; Alesiani, Ornella; Lanzone, Antonio; Apa, Rosanna
Abstract: Objective: To evaluate anti-Müllerian hormone (AMH) concentrations and antral follicle counts (AFCs) in the prediction of pregnancy outcomes after controlled ovarian stimulation among women undergoing intrauterine insemination. Methods: A retrospective study included women with unexplained infertility aged 41 years or younger who attended a fertility clinic in Italy between December 2009 and May 2014. Ovarian stimulation was achieved with recombinant follicle-stimulating hormone or highly purified human menopausal gonadotropin. Receiver operating characteristic curves were generated to predict ongoing pregnancy. The primary outcome was the association between AMH/AFC and ongoing pregnancy, and was assessed by logistic regression. Results: Overall, 276 women were included, of whom 43 (15.6%) achieved ongoing pregnancy. Multivariate analysis showed that women with a serum day-3 concentration of AMH higher than 2.3 ng/mL were more likely to have ongoing pregnancy than were those with a concentration lower than 2.3 ng/mL (odds ratio 5.84, 95% confidence interval 2.38–14.31; P < 0.001). No associations were recorded for AFCs. Conclusion: AMH should be used to predict the pregnancy outcome of intrauterine insemination.